Development of plant extracts as substrates for untargeted transporter substrate identification in Xenopus oocytes - Theodorou, Christos; de-Prado-Parralejo, Victor; Xu, Deyang; Todoroki, Yoshimasa; Svenningsen, Louise; Mori, Tetsuya; Crocoll, Christoph; Hirai, Masami Yokota; Tsugawa, Hiroshi; Nour- Eldin, Hussam Hassan; Halkier, Barbara Ann (Frontiers in Plant Science, 2025)
Amongst the thousands of transport proteins constituting approximately 10% of coding sequences in a genome, only few have an assigned function. Heterologous expression of transporters in combination with the use of plant extracts as complex mixtures of substrates, can be a powerful tool for untargeted identification of plant transporter functionality. In this study, we developed and evaluated four extraction protocols to generate Arabidopsis thaliana seedling extracts for use as substrate mixtures in high-throughput screening of transporters expressed in Xenopus laevis oocytes, a well-established system for transporter studies. To expand chemical space of plant extracts for transporter assay, we prepared Arabidopsis seedlings extracts from liquid culture-grown plants subjected to biotic stress (flagellin 22 and chitin treatments to mimic bacterial and fungal infections) and abiotic stress (phosphorus and nitrogen starvation). Extracts from these treatments were characterized and subsequently combined into a single metabolic mixture to capture treatment-specific metabolites and expand the metabolic space. Toxicity testing of the pooled extract against X. laevis oocytes revealed that a liquid-liquid extraction protocol, facilitating lipophilic compound removal, outperformed single solvent extractions in terms of metabolite repeatability and reduced membrane permeation. Metabolite profiling of the final extract using pure standards, structural databases, and in-silico tools identified over 200 metabolites. Our study highlights the importance of developing metabolically diverse yet low-toxicity plant extracts as a critical step toward advancing plant transporter substrate screening. The optimized extraction protocol in combination with X. laevis oocyte assays, provide a robust platform for the functional characterization of plant transporters, paving the way for deeper insights into plant physiology and metabolism.